An Analysis of Technical Efficiency and Efficiency Factors for Austrian and Swiss Non-Profit Theatres - Marta Zieba (Swiss Journal of Economics and Statistics, 2011)
This article explores the measurement of the production technology and efficiency of the performing arts sector. The stochastic frontier analysis has been used to estimate the technical efficiency scores for 20 Austrian and 30 Swiss non-profit theatres over 36 and 26 years, respectively. The number of visitors and tickets on offer are considered as two alternative measures of artistic output. The results indicate that individual efficiency estimates are very sensitive to the econometric specification of the unobserved heterogeneity of theatres. In particular, econometric techniques which do not account for this heterogeneity produce much lower efficiency levels. The indefinable dimension of artistic output such as theatre-specific quality may also have an important influence on efficiency estimates. The empirical analysis also delivers the first insights into the impact of exogenous factors on technical efficiency such as the number of theatres in the local area, regional differences and the level of public subsidies.
Keywords: Z11; L32; C23; D24; 330; Efficiency Analysis; Stochastic Frontier; Performing Arts; Non-Profit; Austria and Switzerland